Between Expectation and Reality: Factors Determining Financing Sources Preferred and Used by MSMEs - Prihastiwi, Diah Agustina; Sunaningsih, Suci Nasehati; Nugraheni, Agustina Prativi (Universitas Muhammadiyah Magelang, 2021)
MSMEs have a vital role in Indonesian economy and capital is a central issue for them. However, there are still many MSMEs that struggle to grow despite various programs that are instigated to assist this sector. This study aims to provide evidence of mismatch between capital needs/preferences and use for MSMEs. We call that mismatch financing gap. The financing gap was identified through analyses of various MSMEs and owner’s characteristics that affecting preference and use of financing sources by MSMEs. Questionnaires were distributed to MSMEs owners in Magelang City and 121 samples were collected. One-way Anova and Independent t-test were utilized to determine financing sources preferred by MSMEs across different owners and MSMEs characteristics. The output showed that MSMEs at different levels of growth and owners who have different levels of education and experience had different preferences toward bank debt. Furthermore, preference to government assistance and informal sources of financing were driven by MSMEs’ sales and owner’s motivation to start business, respectively. Multiple regression analysis was employed to determine the drivers of MSMEs’ use of financing sources. The results of this study were ownership status, gender, acquisition mode, and education influenced the use of bank loans. Assistance from the government was affected by MSMEs’ type of activity, sales, and experience of the MSMEs’ owners. The use of informal financing sources was affected by motivation and experience of MSMEs’ owners.